PENGARUH LINGKUNGAN ETIKA, INTENSITAS MORAL, DAN KOMITMEN PROFESIONAL TERHADAP INTENSI WHISTLEBLOWING - Syahsa Permata Dwitia; Atiek Sri Purwati; Krisnhoe Rachmi Fitrijati; Umi Pratiwi (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis, Universitas Jenderal Soedirman, 2022)
The purpose of this study was to examine the influence of the ethical environment, moral intensity, and professional commitment on the intensity of whistleblowing of employees at the Purwokerto, Purbalingga, and Banyumas District Attorney's Offices. This type of research is quantitative research. The data collection technique used a questionnaire. The sampling technique in this study used a saturated sample technique. The population of this study were 140 attorneys and the sample used in this study were 128 people. Data analysis technique using multiple linear analysis. The results showed: (1) The ethical environment has a positive and significant effect on whistleblowing intentions, (2) Moral intensity has a positive and significant effect on whistleblowing intentions, (3) Professional commitment has a positive and significant impact on whistleblowing intentions.